The Concept of “Aesthetic Experience” in M. Dufrenne’s Aesthetics - Parulskienė, Vijolė (Problemos, 1986)
The concept of “aesthetic experience” in the works of M. Dufrenne, the French scholar, is analysed. M. Dufrenne treats the concept phenomenologically, relating it to the existential a priori. Only in the view of the latter he defines the essence and the specificity of the aesthetic experience.